2018
DOI: 10.1016/j.resourpol.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in implementing the corporate responsibility to respect human rights in the context of project-induced displacement and resettlement

Abstract: Challenges in implementing the corporate responsibility to respect human rights in the context of project-induced displacement and resettlement van der Ploeg, Lidewij; Vanclay, Francis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
0
27
0
2
Order By: Relevance
“…With a wide range of actions possible, it can be complex for a company to consider what it should do in any particular situation. Drawing on a range of sources [5][6][7]13,20,29,80,[85][86][87][109][110][111][112] and reflecting on our own experiences, it is possible to distil the key general principles companies and other organizations should consider in deciding the actions they could use to help them gain a social license to operate and grow. In addition to observing local laws and complying with appropriate international standards, organizations seeking a social license to operate must:…”
Section: Conclusion: Getting a Social License Requires Taking Communmentioning
confidence: 99%
See 2 more Smart Citations
“…With a wide range of actions possible, it can be complex for a company to consider what it should do in any particular situation. Drawing on a range of sources [5][6][7]13,20,29,80,[85][86][87][109][110][111][112] and reflecting on our own experiences, it is possible to distil the key general principles companies and other organizations should consider in deciding the actions they could use to help them gain a social license to operate and grow. In addition to observing local laws and complying with appropriate international standards, organizations seeking a social license to operate must:…”
Section: Conclusion: Getting a Social License Requires Taking Communmentioning
confidence: 99%
“…The land acquisition needed for projects to proceed also tends to be an activity with considerable potential to create human rights risks and social impacts, especially when expropriation is used [5,6,29,39]. Noting that forced eviction is a gross violation of human rights, two key international documents have been produced to guide companies involved in displacement and resettlement: a United Nations Factsheet on Forced Evictions [53] and the United Nations Basic Principles and Guidelines on Development-Based Evictions and Displacement [54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited knowledge by oil palm companies about how to contribute to the development of sustainable communities or how to deal with the challenges in implementing SSCD. The lack of research about community development in oil palm reflects a general trend that the company perspective has been insufficiently considered in academic literature [68].…”
Section: Issues Associated With Oil Palm and Industrial Timber Plantamentioning
confidence: 99%
“…One expectation of the UNGP is that all companies, projects and major activities (including any impact assessment and resettlement process) should have a grievance redress mechanism. Research undertaken for the development of the UNGP and other research have revealed that situations where companies deliberately intend to harm communities are rare, however harm frequently happens as a result of neglect, ignorance or a lack of proper consideration of social issues by companies (van der Ploeg and Vanclay 2018). It is argued that, if projects have installed effective feedback procedures (grievance redress mechanisms) and act in response to such feedback, many issues could be resolved before they escalate (United Nations 2011; van der Ploeg and Vanclay 2017;Vanclay and Hanna 2019).…”
mentioning
confidence: 99%